Effects of participatory ‘A’rt-Based Activity On ‘Health’ of Older Community-Dwellers: results from a randomized control trial of the Singapore A-Health Intervention - Ho, Andy Hau Yan; Ma, Stephanie Hilary Xinyi; Tan, Michael Koon Boon; Bajpai, Ram; Goh, Shannon Shuet Ning; Yeo, Gabriellia; Teng, Alicia; Yang, Yilin; Galéry, Kévin; Beauchet, Olivier (Frontiers in Medicine, 2023)
Introduction: The practice of participatory art has been found to support the promotion, prevention, and management of health across the lifespan. However, clinical trials investigating the benefits of creative activities curated with and conducted in museums among older adults in East Asia remains limited. Methods: The current research utilized a single-site, open-label randomized control trial (RCT) to evaluate a standardized Participatory ‘A’rt-Based Activity On ‘Health’ of Older Community-Dwellers – the Singapore A-Health Intervention. Outcome measures include frailty as assessed by the Centre of Excellence on Longevity Self-administered Questionnaire, wellbeing as assessed by the Warwick-Edinburgh Mental Wellbeing Scales, and quality of life as assessed by the EuroQol-5D. 112 participants aged 60 and above were randomized into the intervention group (n=56) or an inactive control group (n=56). Participants completed four standardized online self-administered assessments at baseline, 5-week, 9-week and 12-week follow-up during the intervention period. (ClinicalTrial.gov ID: NCT05945589) Results: Linear mixed model analyses revealed no statistically significant differences between the intervention group and control group for all outcome measures. However, within the intervention group, a consistent significant reduction in frailty was observed across time from baseline to 9 weeks (MD -0.44, 95% CI -0.85 to -0.039, p=0.032), 5-weeks to 9-weeks (MD -0.64, 95% CI -1.03 to -0.24, p=0.002), and 5-weeks to 12 weeks (MD -0.51, 95% CI -0.91 to -0.10, p=0.014). Moreover, the post-test mean wellbeing score in the intervention group significantly improved over time at 9-week (MD 1.65, 95% CI 0.09 to 3.22, p=0.039) and 12-week (MD 2.42, 95% CI 0.67 to 4.16, p=0.006) as compared to baseline scores. Discussion: The findings demonstrate the potential of a structured art and museum-based intervention as a resource for promoting health among ageing populations. Such benefits transcend social, cultural, and societal contexts.